Insecticidal effect of plant extracts on two termite species - Elsayed, G (published online, 2011)
The insecticidal contact activity of two desert plant extracts, Withania somnifera and Solanum incanum (Tubiflora: Solanaceae) was tested against the workers of the two species, Amitermes messinae and Microtermes najdensis (Isoptera: Termitidae). The insects were exposed to the plant extracts on Petri dishes (10 cm diameter) for 30 min. Mortality was calculated after 24 h. Crude extract of S. incanum leaves was more toxic to the two species of termites than W. somnifera.
Full text
Keywords: crude extract; desert plants; Solanaceae; termites; bioassay; mortality